Transfers of anti-Waldensian material from a polemical treatise to a didactic text - Reima Välimäki (My University, 2022)
Ulrich von Pottenstein translated Petrus Zwicker’s anti-Waldensian treatise Cum dormirent homines (1395) in his large catechetical encyclopaedia (ca. 1410), written in Early New High German. The translation was dispersed in different chapters, transforming the reading experience of the anti-heretical work but at the same time adding a polemical element to a pastoral text. The article discusses the historical context of Zwicker’s original Latin treatise and Ulrich’s translation, in particular the inquisitions against Waldensians that Zwicker led in Austria in the 1390s, as well as Ulrich’s ecclesiastical career. The second part of the article explores solutions Ulrich had to employ when he translated a text for a lay audience that was not only polemical but also required from its readers a basic understanding of exegesis. Finally, the reasons for Ulrich’s decision to translate Zwicker and the composite nature of the pastoral-didactic text with polemical passages is discussed. As for polemical treatises in general, the motivation behind Ulrich’s translation was to defend the Church against its enemies. Ulrich’s vernacular text had potential to extend the audience of a Latin anti-heretical treatise, but his catechetical encyclopaedia was too large and tedious to read to ever become a popular work. The article proposes that the polemical nature of the original was not mitigated in the process. On the contrary, Ulrich does not shy away from using denigrating or violent language, and polemical style is an essential part of his catechesis. A further study of polemical style in late-medieval pastoral and didactic works, especially vernacular texts, is proposed as a promising area of future research.